Recreating Place: Charles Fothergill and the Limits of Travel Writing - Pam Perkins (Humanities)
In 1806, Charles Fothergill, a young man with a strong interest in natural history, set out on a seven-month tour of Orkney and Shetland. His goal was to write a book about the islands that would emulate the work produced by the earlier traveller Thomas Pennant on Wales and mainland Scotland. Despite his ambition, Fothergill never succeeded in completing his book. His surviving manuscripts, which range from a rough working journal covering one part of his journey to some comments on botany that seem ready to go to press, suggest some of the difficulties that he might have found both in constructing a coherent narrative of his travels and in recreating a version of Pennant’s antiquarian and scientific travels at a time when tastes in travel writing were shifting to focus more on the pleasures of landscape and aesthetics.